OpenStudy (anonymous):

Check? Indicate which property is illustrated in Step 1. Step 1 8 - 7x - 8 + 8x = (8 - 7x) + (-8 + 8x) Step 2 = (8 - 7x) + (8x - 8) Step 3 = 8 + (-7x + 8x) - 8 Step 4 = 8 + (-7 + 8)x - 8 Step 5 = 8 + x - 8 Step 6 = x + 8 - 8 Step 7 = x + 0 Step 8 = x distributive identity associative commutative @iambatman @jadaaa @e.mccormick @campbell_st @aaronq @bibby

3 years ago
OpenStudy (anonymous):

A?

3 years ago
OpenStudy (anonymous):

@mathgeek27 @mathmath333

3 years ago
OpenStudy (anonymous):

Actually it was associative.

3 years ago
OpenStudy (anonymous):

Associative property, because just think about it, if you have (x+y)+z it's the same thing as x+(y+z) because it associates, forming groups.

3 years ago
Similar Questions: